2020
DOI: 10.1111/wre.12452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intra‐row cruciferous surrogate weed growth on crop yield in organic spring cereals

Abstract: The standard cropping strategy used to grow organic cereals in Northern Europe is to sow at an inter-row spacing of 12.5 cm; weeds are controlled physically by implementing both pre-and post-emergence weed harrowing. Pre-emergence harrowing is performed after sowing and before crop emergence, reducing the number of weeds that establish alongside the crop. Postemergence harrowing is performed after crop emergence (Lundkvist, 2009; Rasmussen, 2004). Weed harrowing has both its advantages and disadvantages, as ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Intra-row weeds remain a problem when inter-row hoeing, especially tallgrowing cruciferous species that can reduce crop yields markedly, as shown in Table 1 (Melander and McCollough, 2020). Mixed intra-row weed populations with a greater proportion of weed species short in stature may not be as competitive as seen in a Danish study with inter-row hoeing, performed in 11 weedy fields with organic spring cereals.…”
Section: Inter-row Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-row weeds remain a problem when inter-row hoeing, especially tallgrowing cruciferous species that can reduce crop yields markedly, as shown in Table 1 (Melander and McCollough, 2020). Mixed intra-row weed populations with a greater proportion of weed species short in stature may not be as competitive as seen in a Danish study with inter-row hoeing, performed in 11 weedy fields with organic spring cereals.…”
Section: Inter-row Cultivationmentioning
confidence: 99%
“…White mustard (Sinapis alba) was used to simulate cruciferous intra-row weed growth typical for Raphanus raphanistrum, Sinapis arvensis, and Brassica rapa. Intra-row surrogate weeds Sinapis alba (plants m −2 ) are defined as those plants growing in the uncultivated area 2.5 cm to either side of the crop row's center (Melander and McCollough, 2020) also means that the intensity of cultivation increases, and severe crop injuries become more likely since the crop is also treated. The most obvious advantage of stacking tools is that weed problems requiring several intense passes with a single tool might be controlled in one pass when employing the stacking concept.…”
Section: Stacking Tools For Intra-row Cultivationmentioning
confidence: 99%
“…Excluding EXP 2019 WMT tineharrow RS 15 ambient weed biomass results, within the range of crop densities tested (CD 200 to CD 500 ), intrarow surrogate and ambient weed biomass were reduced by 49% to 82% and 53 to 86%, respectively (Figure 3). The effect that increasing seeding rate has on suppressing intrarow weeds is an important result, one that improves our understanding of how to limit potential yield and crop quality losses resulting from remaining competitive intrarow weeds in hoed cereals (Melander and McCollough 2020). Percent reduction of intrarow weed biomass was slightly higher for ambient weeds compared with surrogate weeds, comprising differences of 4.5% and 4.3% at CD 300 in EXP 2019 and EXP 2020 , respectively.…”
Section: Intrarow Weed Biomassmentioning
confidence: 99%
“…Depending on the competitive abilities of weed species present, remaining intrarow weeds can compete intensely with the crop due to their close proximity. In hoed spring barley (Hordeum vulgare L.), Melander and McCollough (2020) reported that an intrarow surrogate weed, white mustard (Sinapis alba L.), reduced crop yields by 4% to 7 %, 14% to 26%, and 21% to 40% when densities of 5, 25, and 50 plants m −2 were recorded, respectively. Therefore, it is necessary to investigate further how intrarow weed management can be improved to optimize the hoed cereal system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation